Pregnancy Complications and Outcomes in Obese Women with Gestational Diabetes - Gitana Ramonienė; Laura Malakauskienė; Eglė Savukynė; Laima Maleckienė; Greta Gruzdaitė (Medicina)
Background and Objectives: To assess pregnancy and delivery complications in obese women with gestational diabetes mellitus (GDM) and neonatal weight and condition after birth. Materials and Methods: A retrospective tertiary referral centre study included all cases of GDM in the Department of Obstetrics and Gynaecology of the Lithuanian University of Health Sciences (LUHS) Birth Registry from 1 January 2019 to 31 December 2019. We included 583 women with GDM and singleton pregnancies. Women were divided into two groups according to their pre-pregnancy weight: 202 were obese (BMI ≥ 30 kg/m2), and 381 were weight (BMI 18.5–24.9 kg/m2). Survey data were analysed using IBM SPSS Statistics 26.0 and MS Excel 2016 software. A value of p < 0.05 was considered significant. Results: Fasting glycaemia was significantly higher in obese women with GDM than in normal-weight women with GDM (p < 0.001). In addition, fasting glycaemia was higher in obese women with GDM requiring insulin correction than in normal-weight women (p = 0.006). OGTT 0-min glycaemia was higher in obese than in non-obese women with gestational diabetes (p < 0.001). Women with pre-pregnancy obesity had a higher incidence of primary hypertension (p < 0.001), hypertensive disorders in pregnancy (p < 0.001), gestational cholestasis (p = 0.002), polyhydramnios (p < 0.001), induced labour (p < 0.001), and caesarean section (p = 0.015), with emergency caesarean sections being more frequent than planned caesarean sections (p = 0.011) compared to normal-weight women with GDM. Labour dystocia (p = 0.003) and foetal distress (p = 0,019) were more common during labour in obese women. Neonates of these women more often had macrosomia (p < 0.001) and lower Apgar scores at 1 min (p = 0.024) and at 5 min (p = 0.024) compared to neonates of normal-weight women. Conclusions: Obese women with GDM experience more pregnancy complications than normal-weight women with GDM.